2022
DOI: 10.3892/br.2022.1578
|View full text |Cite
|
Sign up to set email alerts
|

Currently available molecular analyses for personalized tumor therapy (Review)

Abstract: Targeted therapies are becoming more common and genetic tumor profiling is becoming more precise and affordable. The aim of the present review was to demonstrate the importance of molecular analyses in tumors, summarize the current situation, provide an outlook on how to improve diagnosis to facilitate individualized therapy, including the use of specific methodologies for tumor marker analysis to improve patient treatment. Most predicted metabolomic and proteomic biomarkers have not progressed from the labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…In the present study, cell viability was measured after 72 h treatment with the extracted samples. The cytotoxic agent in the extracted samples may affect the molecular cell mechanisms and disturb cell division ( 47 ). Therefore, it could be hypothesized that not all surviving cells after treatment could proliferate under those conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, cell viability was measured after 72 h treatment with the extracted samples. The cytotoxic agent in the extracted samples may affect the molecular cell mechanisms and disturb cell division ( 47 ). Therefore, it could be hypothesized that not all surviving cells after treatment could proliferate under those conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, the present results indicated that CTPPs had cytotoxic activity against the viability of MCF-7 cells. The cytotoxic effects of CTPPs were probably responsible for suppressing of the proliferating cells, as a recent report demonstrated that cytotoxic drugs could disturb the process of cell division ( 47 ). Even though the results on cell proliferation were inferior compared with those in the positive control group, this was a beneficial result in terms of cancer treatment, because cell proliferation is a critical process of cell division.…”
Section: Discussionmentioning
confidence: 99%
“…The construction of the interaction operator I c is similar to that of I i , and the interaction operator I n has a specific term related to the effect of the normal cell reservoir. In Equation (10), the second term represents the introduction of normal cells of activity u into the system at a rate given by the consumption of normal cells k cn (u − u )H(u − u ) associated with the interaction between a cancer cell and a normal cell. The activity u of the introduced normal cell is sampled from the distribution P n (u) given in Equation ( 1).…”
Section: Thermostatted Kinetic Theory Frameworkmentioning
confidence: 99%
“…Biological models traditionally describe the interactions between cancer and the immune system at either the molecular scale [8][9][10] or the macroscopic scale [11,12]. Typically, these models incorporate intricate interaction networks between numerous actors, such as molecules, tissues, organs, and the lymphatic and vascular systems.…”
Section: Introductionmentioning
confidence: 99%